Clustering of job strain, effort−reward imbalance, and organizational injustice and the risk of work disability: a cohort study - Juvani, Anne; Oksanen, Tuula; Virtanen, Marianna; Salo, Paula; Pentti, Jaana; Kivimäki, Mika; Vahtera, Jussi (Scandinavian Journal of Work, Environment & Health, 2018)
' ' OBJECTIVES ': 'The aim of this study was to examine the association between co-occurring work stressors and risk of disability pension. ' ' METHODS ': 'The work stressors job strain, effort−reward imbalance (ERI), and organizational injustice were measured by a survey in 2008 of 41 862 employees linked to national records of all-cause and cause-specific disability pensions until 2011. Co-occurring work stressors were examined as risk factors of work disability using Cox regression marginal models. ' ' RESULTS ': 'Work stressors were clustered: 50.8% had no work stressors [observed-to-expected ratio (O/E)=1.2], 27.4% were exposed to one stressor (O/E=0.61–0.81), 17.7% to two stressors (O/E=0.91–1.73) and 6.4% to all three stressors (O/E=2.59). During a mean follow-up of 3.1 years, 976 disability pensions were granted. Compared to employees with no work stressors, those with (i) co-occurring strain and ERI or (ii) strain, ERI and injustice had a 1.9–2.1-fold [95% confidence interval (CI) 1.7–2.6] increased risk of disability retirement. The corresponding hazard ratios were 1.2 and 1.5 (95% CI 1.0–1.8) for strain and ERI alone. Risk of disability pension from depressive disorders was 4.4–4.7-fold (95% CI 2.4–8.0) for combinations of strain+ERI and strain+ERI+injustice, and 1.9–2.5-fold (95% CI 1.1–4.0) for strain and ERI alone. For musculoskeletal disorders, disability risk was 1.6–1.9-fold (95% CI 1.3–2.3) for strain+ERI and ERI+injustice combinations, and 1.3-fold (95% CI 1.0–1.7) for strain alone. Supplementary analyses with work stressors determined using work-unit aggregates supported these findings. ' ' CONCLUSIONS ': 'Work stressors tend to cluster in the same individuals. The highest risk of disability pension was observed among those with work stressor combinations strain+ERI or strain+ERI+injustice, rather than for those with single stressors.
Keywords: cohort study; early exit; early retirement; effort−reward imbalance; ERI; job strain; mental health; occupational health practice; organizational injustice; work disability; work stress; work stressor